Labeling of Genetically Modified Food and Consumers’ Rights - Vujisić, Dragan; Mihajlović, Borko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
The legal regulation of genetically modified food directly affects consumers, since they are the ones who encounter genetically modified food on the shelves every day. At the beginning, authors indicate that there are huge differences between legal regulation of genetically modified food in the United States and in the European Union. These differences result in different labeling regimes in those two systems of genetically modified food regulation. Authors consider several factors from which depend efficiency of the labeling regime, and labels’ influence on the actual realization of basic consumers’ rights. Authors will analyze these factors in the paper, such as: label complexity, opting for positive or negative labeling regime, whether labeling regime is mandatory or voluntary, etc. In the conclusion authors give recommendations to the Serbian legislator, and propositions for changes in current domestic legal regulation, which would improve realization of basic consumers’ rights in relation with genetically modified food.